Reserva Extrativista Chocoaré - Mato Grosso: vivências e perspectivas para a Comunidade de Bom Intento (2002 – 2023) - SILVA, Helder Dias da (2024)
This article analyzes the changes that have occurred in the experiences of residents of Vila de Bom Intento, municipality of São João de Pirabas/Pa, who live on the banks of the Maracanã and Chocoaré Rivers and who use the rivers as a route for extractivism in search of means of subsistence, and from an analysis understands what changed in the lives of residents in the use of the environment, after the creation of the Chocoaré-Mato Grosso Extractive Reserve in 2002. And in order to achieve certain objectives, it was necessary delve deeper into theoretical references through research carried out on the legislation of Extractive Reserves existing in Brazil and especially the Chocoaré-Mato Grosso Extractive Reserve. And also to conclude this research, the importance of the role of the residents of this community in building memories of the Village is highlighted. The methods used in data collection were: interviews with some residents using oral speech as the main source for the results of this work, as well as bibliographical consultations, photos, maps and websites.